REVIEW ARTIKEL : STANDAR PELAYANAN KEFARMASIAN DI APOTEK BERDASARKAN PERMENKES NOMOR 73 TAHUN TAHUN 2016 DI INDONESIA - Annafiatuzakiah; Clara Ritawany Sinaga, Esty Elvinda (CV. Adiba Aisha Amira, 2025)
Drug information services are activities to provide and give information, independent, accurate, unbiased, current and comprehensive drug recommendations so that medication errors occur by pharmacists to patients and the public who need drug information so that they can increase the success of therapy, maximize the effects of therapy and minimize the risk of side effects of drugs. Pharmacies are established as one of the pharmaceutical service facilities that provide drugs and medical devices with guaranteed quality and safety. Pharmaceutical services are carried out by pharmacists who are one of the drug information services (PIO). PIO is an activity carried out by pharmacists in providing impartial information about drugs, and is critically evaluated and proven to be the best in all aspects of use. This study aims to be data for consideration of pharmaceutical service analysis in Pharmacies. This study used the literature method. search on research journals, 25 research journals published from 2017-2022. The results of the study show that most of the pharmaceutical services by pharmacists in pharmacies are in accordance with Permenkes No 73 of 2016.